Integrated estimation of mathematical knowledge of students at semester time - Krylovas, Aleksandras; Raulynaitis, Juozas (Lietuvos matematikos rinkinys, 2004)
The experiment of integrated estimation of students mathematical knowledge at semester time in Vilnius Gediminas Technical University is described.